Aristotle’s ‘Platonic’ Egypt - Donato, Marco (Hyperboreus, 2024)
The presence of Egypt in Aristotle’s corpus is twofold. On one side, notices about the land and its inhabitants – be them humans or beasts – are vastly exploited in scientiﬁc works such as the History of Animals. On the other hand, ancient Egypt is less often but more signiﬁcatively mentioned as a uniﬁed cultural and historical horizon, opposed, contrasted or simply compared with the Greek world. The paper examinates some examples of this tendency, especially focusing on Aristotle’s Politics, Metaphysics and Meteorologica. Insisting on the association with time, tradition and memory, Aristotle treats Egypt as a paradigmatic and semi-legendary background used to evoke and discuss the central issues of acquisition, persistence and renewal of knowledge over time. Doing this, whilst reemploying other elements from ethnographical and historical sources, the Stagirite stays faithful to Plato’s literary use of Egypt and more speciﬁcally to the Egyptian settings evoked in the Phaedrus and in the Timaeus, but feels free to correct his model and to introduce novel elements in a similar theoretical framework.